MENGUNGKAP PRAKTIK AKUNTANSI DI MASJID BERBASIS NILAI-NILAI KEARIFAN LOKAL GORONTALO - Mohamad Anwar Thalib; Sri Mandalika Mosu; Siskawati Yunus Njuu (Universitas Nusa Cendana, 2022)
This study aims to reveal the mosque's accounting practices based on Gorontalo Islamic cultural values. The type of method used is qualitative, with data analysis techniques using the Miles and Huberman model. The results showed that; First, the capital for operating mosque activities comes from donations from the community and mosque congregations; second, the capital is used to finance worship activities and renovate mosque buildings; third, the form of accountability for the use of funds is carried out by mosque administrators through simple accounting records and reporting the use and income of funds every Friday. mosque accounting practices in the form of giving funds, using funds, simple recording, and accountability of funds are driven by the spirit of sincerity (ihilah) and mutual trust (paracaya), and responsibility (dudaha). These values are advice that is often conveyed by parents through the expression (lumadu)